On the mechanism of genotoxicity of ethephon on embryonic fibroblast cells. (24th March 2017) - Hodjat, Mahshid; Baeeri, Maryam; Rezvanfar, Mohammad Amin; Rahimifard, Mahban; Gholami, Mahdi; Abdollahi, Mohammad
Abstract: Ethephon is one of the most widely used plant growth regulator in agriculture that its application has been increased in recent years. Many reports have raised concern over the safety of this organophosphorus compound. The aim of the current study was to assess the potential genotoxic effect of ethephon on murine embryonic fibroblast (MEF) cell line, using two genotoxicity endpoints: γH2AX expression and comet assay. γH2AX served as an early and sensitive biomarker of genotoxic damage. Oxidative stress biomarkers, including reactive oxygen species (ROS), lipid peroxidation (LPO) and total antioxidant capacity were also examined. The results showed a significant increase in cell proliferation, 24 h post-treatment with 10, 40, 160 μg/ml ethephon, while at the higher concentrations cytotoxic effect was observed. The γH2AX expression and γH2AX foci count per cell were significantly increased at non-cytotoxic concentrations of ethephon, accompanied with increased DNA damage as illustrated by comet assay. LPO and ROS levels were elevated only at 160 μg/ml and higher doses. The results interestingly showed that low non-cytotoxic doses of ethephon promoted DNA damage inducing cell proliferation, raising the possibility of ethephon mutagenicity. The genotoxic effect of ethephon at low doses might not relate to oxidative damage and that increased in the level of ROS and LPO generation at higher doses could account for the cytotoxic effect of ethephon. Taken together, our study provides strong in vitro evidence on potential genotoxicity of ethephon at low doses. More precise studies are needed to clarify the mutagenic effect of chronic exposure to ethephon.